Cirsoid Aneurysm of the Scalp: A Case Report - Mayur Vinod Barhate (Indian Journal of Neurosurgery, 2016)
Abstract Cirsoid aneurysms (arteriovenous malformations [AVMs]) of the scalp are rarely encountered in neurosurgical practice. Patients with AVM of the scalp present clinically at times with headache and a small innocuous-looking subcutaneous scalp lump or a large, pulsatile mass with or without bruit, which has a propensity to massive hemorrhage. Complex vascular anatomy and interconnections, high shunt flow, and possible cosmetic complications tend to make their management difficult. We report a rare case of young man who presented with progressively enlarging swelling over left fronto-temporo-parietal and occipital region of the scalp since 8 years. Digital subtraction angiography of internal and external carotid vessels revealed high-flow, complex left parietal scalp AVM supplied by multiple tortuous feeders from left superficial temporal artery (STA), left middle meningeal artery, left occipital artery with collateral supply from right occipital artery, and right STA. Drainage into external jugular vein through multiple tortuous frontal, temporal, and occipital scalp veins with venous varix. Being high-flow shunt and because of suspected cosmetic complications, surgical excision was considered.